Yahoo Web Search

  1. Sort by

  1. (k+5)^2 -12k(k+2) (k+5)(k+5)-12k(k+2) k^2+10k+25-12k(k+2) k^2+10k+25-12k^2-24k -11k^2+10k+25-24k -11k^2-14k+25 is the answer

    5 Answers · Education & Reference · 08/11/2009

  2. In mathematics, k + k + k + k + k = 5k. => Let me explain this to you. There...k's in the expression: k + k + k + k + k which k is common, then factor out k, i.e. (1 + 1 + 1 + 1 + 1)k = 5 * k = 5k. Or if you're familiar with this...

    4 Answers · Education & Reference · 01/11/2013

  3. = (k - 7)² = k(k) + k(- 7) - 7(k) - 7(- 7) = k² - 7k - 7k + 49 = k² - 14k + 49 Answer: k² - 14k + 49

    5 Answers · Education & Reference · 26/02/2010

  4. k = 0 is clearly a value for which the system has infinitely many solutions. Suppose k ≠ 0. -- k -k 0 k 0 1 1-k 0 k -4 k-1 3 -- 1 -1 0.... We still get no solutions if k = 1. Hence, we get infinite solutions if k...

    1 Answers · Education & Reference · 02/07/2013

  5. k^2 + 2k - 15 = 0 This will factor easily. Q: what are two ...with a PRODUCT of -15, and a SUM of 2? A: 5 and -3 (k + 5)(k - 3) = 0 One of the factors must equal zero. (i) If...

    4 Answers · Education & Reference · 22/10/2011

  6. k - 5 1/8 = 9 3/10 k - 41/8 = 93/10 k = 93/10 + 41/8 k = (93 * 4 + 41 * 5) / 40 k = 577/40 k = 14.425

    2 Answers · Education & Reference · 18/11/2014

  7. k(x) = 6x^2 - 6x ---- I am assuming your problem is... 2....but if it is 6 times 2, then disregard this post. k(5) = 6(5^2) - 6(5) k(5) = 6(25) - 30 k(5) = 150 - 30 k(5) = 120 k(-4) = 6(-4^2...

    3 Answers · Education & Reference · 10/05/2014

  8. k/3 - 6 = 4 Add six onto both sides: k/3 = 10 Multiply each side by three: k = 30 And k = 30 is your answer.

    3 Answers · Education & Reference · 06/05/2009

  9. 5(k + 1) = 3k + 12; distribute the 5 5k + 5 = 3k + 12; subtract 3k from both sides 5k...5 - 5 = 12 - 5; simplify 2k = 7; divide each term by 2 2k/2 = 7/2; simplify & solve k = 7/2 <---------Answer Check: 5(7/2 + 1) = 3(7...

    5 Answers · Education & Reference · 15/04/2011

  10. k/6 = 5/6 -2 since 2 = 12/6 k/6 = (5-12)/6 k/6 = -7/6 multiply both sides by 6 k = -7

    2 Answers · Education & Reference · 17/11/2012

  1. Ad
    related to K
  1. Try asking your question on Yahoo Answers